Influence of thick soft superficial layers of seabed on ground motion and its treatment suggestions for site response analysis - Jiang Qifeng (De Gruyter, 2021)
The thick soft superficial layers of the seabed greatly influence ground motion generally. It is worth studying how to find out the influence of these soft layers on ground motion parameters and determine reasonable seismic fortification parameters for ocean engineering. Numerical experiments of site response analysis are designed using two offshore engineering sites in this study. First, the borehole profiles are selected and stripped layer by layer to generate new profiles. Second, 108 acceleration time histories are synthesized which basically represent the diversity of input motions’ amplitude and frequency. Third, a method that can automatically calculate characteristic periods and normalize response spectra is created to improve calculation efficiency. Fourth, peak accelerations, response spectra, and characteristic periods at different depths of the profiles with different stripping depths are calculated. The results show that the thick soft superficial layers can significantly decrease peak ground accelerations and increase characteristic periods, resulting in serious “low-fat” response spectra. The situation can be greatly improved by stripping off the soft superficial layers. After stripping off the thick soft superficial silt layers, if stripping is continued further, the variation in the superficial amplification ratios of peak accelerations and superficial characteristic periods will no longer be drastic, and the superficial amplification ratios and characteristic periods both tend to be mostly the same. The relative deviation of the amplification ratio of peak ground acceleration between a profile stripped and that without stripping can be 143%, and it can be 83% for characteristic period. It is advisable to strip off thick soft superficial layers to perform site response analysis, and the shear force at the bottom of the silt should be considered in engineering based on local seismic activity level, and the silt’s and the structure’s physical parameters.